Air quality trend and proposal of a web application for the atmospheric monitoring network in Tabasco, México. - Magaña Villegas, Elizabeth; Díaz López, Mary C.; Ramos Herrera, Sergio; Carrera-Velueta, Jesús M.; Vilchis-Peralta, Osiris J. (TECCIENCIA, 2020)
Air pollution is an increasingly concerning problem given it constitutes a risk for people’s health and the environment. In Mexico, there are some regions where society does not know the conditions of air quality, and in some others this information is not used or analyzed. Hence is important the study of air quality evolution to generate strategies that allow to mitigate adverse effects on population. In this research we analyze the trend of Criteria Air Pollutants (PM10 and O3 and CO), considering the distribution of good, regular and bad days for air quality, as well as the trend of hourly, daily, monthly and annual concentrations in the city of Villahermosa, Tabasco between 2011-2017, with information provided by the State government, in order to design an effective communication mechanism. We obtained air quality indicators based on the official Mexican regulation and the temporal behavior of the pollutants. Additionally, we trained artificial neural network models for the prediction of air pollutant concentration. Finally, we propose the design of a web portal for the communication of air quality. According to the weekly behavior, is shown that we are exposed daily to potential health hazards by any of the air pollutants, also that the second trimester of each year shows the worst conditions and that the pollutants that have a greater contribution to air pollution in the city are CO, PM10 and O3. Likewise, the tendencies of PM10 and O3 indicate a slow decrease of -0.5 ug/m3 -year, -0.0004 ppm-year respectively, which requires a redefinition of government strategies that may potentiate their decrease. In this sense, the web portal is proposed under two main approaches: First, with the purpose of communication, aimed to the society so it can take preventive measures on their exposure to high contamination levels. The second approach is aimed to the academic community and government authorities, with graphic information on the criteria air pollutants’ tendencies, providing analytical elements for structuring environmental policies.